Notch and Transforming Growth Factor-β (TGFβ) Signaling Pathways Cooperatively Regulate Vascular Smooth Muscle Cell Differentiation - Tang, Yuefeng (American Society for Biochemistry and Molecular Biology, 2010)
Notch and transforming growth factor-β (TGFβ) play pivotal roles during vascular development and the pathogenesis of vascular disease. The interaction of these two pathways is not fully understood. The present study utilized primary human smooth muscle cells (SMC) to examine molecular cross-talk between TGFβ1 and Notch signaling on contractile gene expression. Activation of Notch signaling using Notch intracellular domain or Jagged1 ligand induced smooth muscle α-actin (SM actin), smooth muscle myosin heavy chain, and calponin1, and the expression of Notch downstream effectors hairy-related transcription factors. Similarly, TGFβ1 treatment of human aortic smooth muscle cells induced SM actin, calponin1, and smooth muscle protein 22-α (SM22α) in a dose- and time-dependent manner. Hairy-related transcription factor proteins, which antagonize Notch activity, also suppressed the TGFβ1-induced increase in SMC markers, suggesting a general mechanism of inhibition. We found that Notch and TGFβ1 cooperatively activate SMC marker transcripts and protein through parallel signaling axes. Although the intracellular domain of Notch4 interacted with phosphoSmad2/3 in SMC, this interaction was not observed with Notch1 or Notch2. However, we found that CBF1 co-immunoprecipitated with phosphoSmad2/3, suggesting a mechanism to link canonical Notch signaling to phosphoSmad activity. Indeed, the combination of Notch activation and TGFβ1 treatment led to synergistic activation of a TGFβ-responsive promoter. This increase corresponded to increased levels of phosphoSmad2/3 interaction at Smad consensus binding sites within the SM actin, calponin1, and SM22α promoters. Thus, Notch and TGFβ coordinately induce a molecular and functional contractile phenotype by co-regulation of Smad activity at SMC promoters.